2017
DOI: 10.1002/adhm.201700659
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐Regenerative Hydrogel Restores Scarless Skin during Cutaneous Wound Healing

Abstract: The transformation of fibrotic healing process to regenerative one has great potential to fully restore wounded skin. The M2 macrophage phenotype promotes constructive tissue remodeling and instructs tissue repair in a regenerative manner. It is hypothesized that hydrogels that can establish robustness of endogenous cells to regulate M2 phenotype will promote constructive dermal remodeling. Toward this end, a series of dextran‐based bioabsorbable hydrogels are developed and self‐crosslinkable dextran‐isocyanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…Our experimental results showed that the ADM scaffolds promoted adipose tissue formation in the newly reconstituted skin (Figure 7D ). A similar phenomenon has been observed in hydrogel-treated acute skin injuries, in which the hydrogel promotes adipose tissue formation (Sun and Sun, 2017 ). Additionally, M2 polarization in ADM scaffold-treated wounds compared with that in saline-treated wounds greatly reduced the acceleration of fibrous encapsulation to approach normal collagen tissue (Figures 7B,E ).…”
Section: Discussionsupporting
confidence: 75%
“…Our experimental results showed that the ADM scaffolds promoted adipose tissue formation in the newly reconstituted skin (Figure 7D ). A similar phenomenon has been observed in hydrogel-treated acute skin injuries, in which the hydrogel promotes adipose tissue formation (Sun and Sun, 2017 ). Additionally, M2 polarization in ADM scaffold-treated wounds compared with that in saline-treated wounds greatly reduced the acceleration of fibrous encapsulation to approach normal collagen tissue (Figures 7B,E ).…”
Section: Discussionsupporting
confidence: 75%
“…The group found that this material induced polarization to an M2‐like phenotype as characterized by both surface marker expression and cytokine production. Similarly, Sun described the use of a dextran‐isocyanatoethylmethacrylate‐ethylamine (DexIEME) hydrogel to stimulate skin regeneration in both porcine and mouse models . This dextran‐based, bioabsorbale hydrogel was also shown to promote healing at pre‐existing scar sites and promote the formation of hair follicles.…”
Section: Advanced Tissue Engineering Approaches To Regenerate Skinmentioning
confidence: 99%
“…The use of immunomodulatory biomaterials in an implant localizes immunosuppression to the wound site by removing the need for immunosuppressive drugs while having the potential to further reduce poor cosmetic outcomes. Common strategies in immunomodulation for skin regeneration include macrophage polarization (Sun, 2017 ; Castellano et al, 2018 ), the use of glycosaminoglycans (GAGs) (Bhowmick et al, 2017 ; Pezeshki-Modaress et al, 2017 ), and the use of decellularized matrices (Kuna et al, 2017 ).…”
Section: Immunomodulatory Biomaterials For Skin Tissue Engineeringmentioning
confidence: 99%
“…Their sensitivity to stimuli and ubiquity in immune processes makes them a prime target for strategic immunomodulation, with polarization to the M2 type being the goal. For example, dextran-isocyanatoethyl methacrylate-ethylamine (DexIEME) used as a hydrogel scaffold for cutaneous wound healing was shown to be effective in treating both pre-existing scars in mice and deep wounds in porcine animal models by promoting M2 macrophage polarization (Sun, 2017 ). DexIEME first led to differentiation of monocytes into macrophages followed by further polarization of differentiated macrophages to the M2 phenotype in vitro .…”
Section: Immunomodulatory Biomaterials For Skin Tissue Engineeringmentioning
confidence: 99%